2022
DOI: 10.1039/d2cy00486k
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed synthesis of mixed anhydridesviacarbonylative telomerization

Abstract: For the first time, mixed carboxylic anhydrides were accessed directly via homogeneous palladium catalysis from 1,3-butadiene and carboxylic acids. Under carbonylative telomerization conditions, the respective mixed 3,8-nonadienoic anhydrides are formed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, they have been isolated with moderate yields. In the same year, Seidensticker et al [20] reported a new palladium acetate Pd (OAc) 2 ‐catalyzed synthesis of carboxylic acid anhydrides via the telomerization of 1,3‐butadiene and carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%
“…However, they have been isolated with moderate yields. In the same year, Seidensticker et al [20] reported a new palladium acetate Pd (OAc) 2 ‐catalyzed synthesis of carboxylic acid anhydrides via the telomerization of 1,3‐butadiene and carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Seidensticker and co‐workers reported on the carbonylative telomerization of 1,3‐butadiene with carboxylic acids. This produced mixed 3,8‐nonadienoic anhydrides which were directly used as acetylation agents for the synthesis of amides [8] …”
Section: Introductionmentioning
confidence: 99%
“…This produced mixed 3,8nonadienoic anhydrides which were directly used as acetylation agents for the synthesis of amides. [8] Acetic anhydride can be produced via the ketene process, [1] oxidation of acetaldehyde [1] or via the carbonylation of methyl acetate. [1,9] The ketene process can also be used for the synthesis of long chain anhydrides.…”
Section: Introductionmentioning
confidence: 99%